Changing trends in the incidence of juvenile nasopharyngeal angiofibroma: seven decades of experience at King George's Medical University, Lucknow, India. Issue 4 (11th February 2016) - Mishra, A; Mishra, S C
Abstract: Background: The occurrence of juvenile nasopharyngeal angiofibroma is reportedly higher in India than in some other parts of the world, and our centre has seen a four-fold increase in its occurrence across seven decades. Methods: This paper reports a retrospective archival analysis of 701 juvenile nasopharyngeal angiofibroma cases from 1958 to 2013, and considers probable environmental factors in an Indian context that may affect its biology and the global distribution, as reported in the literature. Results: A continuously progressive increase in occurrence was evident, but the rapid rise observed in the current decade was alarming. The world map of juvenile nasopharyngeal angiofibroma incidence does not reflect true global distribution given the paucity of reporting. Our centre has dealt with approximately 400 cases in the last 24 years. Conclusion: With the alarming increase in juvenile nasopharyngeal angiofibroma incidence, there is a need for a registry to define its epidemiology. The world literature needs to reflect the status of juvenile nasopharyngeal angiofibroma incidence in the third world as well. Environmental factors known for hormone disruptive actions may influence its occurrence. Such aspects need to be considered to plan specific prevention policies.